Integration of Pedagogical Content Knowledge (PCK) and Montessori Approach in Inclusive Learning in Early Childhood Education - Pamularsih, Yustina Tri Budi; Dhieni , Nurbiana; Pujiastuti , Sri Indah (Jurnal Pendidikan Anak, 2025)
Inclusive education in early childhood requires adaptive and meaningful teaching strategies to accommodate the diverse needs of students. This study aims to explore the integration of Pedagogical Content Knowledge (PCK) in the Montessori approach by PAUD teachers in inclusion classes. The method used was qualitative descriptive, involving six teachers at Aluna Montessori School through observation, semi-structured interviews, and documentation studies. Data analysis was performed using Miles & Huberman's interactive model and triangulation. The results showed that teachers were able to integrate Content Knowledge (CK), Pedagogical Knowledge (PK), and Pedagogical Content Knowledge (PCK) in each stage of the learning context in a contextual and multisensory manner. This integration strengthens the independence, emotional engagement, and conceptual understanding of children, including children with special needs. These findings highlight the importance of teacher professional development, based on formative observation and collaborative reflection, in the context of Montessori inclusive education